2012
DOI: 10.1038/nrm3312
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional integration of metabolism by the nuclear sterol-activated receptors LXR and FXR

Abstract: Nuclear receptors are integrators of hormonal and nutritional signals, mediating changes to metabolic pathways within the body. Given that modulation of lipid and glucose metabolism has been linked to diseases including type 2 diabetes, obesity and atherosclerosis, a greater understanding of pathways that regulate metabolism in physiology and disease is crucial. The liver X receptors (LXRs) and the farnesoid X receptors (FXRs) are activated by oxysterols and bile acids, respectively. Mounting evidence indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
560
2
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 651 publications
(580 citation statements)
references
References 122 publications
(151 reference statements)
13
560
2
5
Order By: Relevance
“…While several changes were observed in the expression of bile acid transporters, we did not observe any significant changes in the liver or plasma concentrations of bile acids in the HFD group. Nevertheless, it is possible that HFD-induced changes could have resulted in bile acid retention at an earlier time point as FXR activation leads to negative feedback inhibition to normalise bile acid levels by increasing the efflux of bile acids from hepatocytes and decreasing de novo synthesis of bile from cholesterol (51,52) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While several changes were observed in the expression of bile acid transporters, we did not observe any significant changes in the liver or plasma concentrations of bile acids in the HFD group. Nevertheless, it is possible that HFD-induced changes could have resulted in bile acid retention at an earlier time point as FXR activation leads to negative feedback inhibition to normalise bile acid levels by increasing the efflux of bile acids from hepatocytes and decreasing de novo synthesis of bile from cholesterol (51,52) .…”
Section: Discussionmentioning
confidence: 99%
“…The results from the present study show that total cholesterol levels were significantly elevated in the HFD group, as well as an increased expression level of the cholesterol transporters Abca1 and Abcg5. The nuclear receptor LXR, which is activated by cholesterol derivatives such as oxysterols (51) , is involved in the induction of the expression levels of Abca1, Abcg5, Abcg8 and Cyp7a1, leading to increased serum cholesterol levels. The expression of Cyp7a1, which was not significantly affected by the HFD in the present study, is regulated by both LXR and FXR (53,54) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent evidence has demonstrated that VDR has a protective role in cardiac hypertrophy [152] , heart failure after cardiac remodeling [153] and MI/R injury [154] . LXRs have two receptor subtypes-LXRα (NR1H3) and LXRÎČ (NR1H2)-that exhibit different expression patterns and perform different functions [155] . Recent evidence suggested that LXRα/LXRÎČ are both expressed in the cardiovascular system.…”
Section: Endoplasmic Reticulum Stress Is Involved In the Developmentmentioning
confidence: 99%
“…activation of CYP7A1 by the liver X receptor (LXR) occurs in the mouse but not in man (the reader is directed to [7] for a recent review of this area). Many other transcription factors and intracellular 8 signalling pathways have been implicated in the regulation of CYP7A1, at least in some species [7].…”
Section: Cyp7a1mentioning
confidence: 99%
“…For details of these studies the reader is directed to [7,8] for recent reviews. In this paper we review the studies to date on the role of epigenetics in regulation of GROS and summarise the evidence for this (Table 1).…”
Section: Introductionmentioning
confidence: 99%